METABOLIC SYNDROME IN ACUTE CORONARY SYNDROME - Bhalli, Muhammad Asif; ., Muhammad Aamir; ., Ghulam Mustafa (Pakistan Armed Forces Medical Journal, 2011)
Objective: To determine the frequency of metabolic syndrome in male patients presenting with acute coronary syndrome Study design: A Descriptive study Place and duration of study: Armed Forces Institute of Cardiology and National Institute of Heart Diseases, Rawalpindi, from October 2007 to September 2008. Patients & Methods: Male patients with acute coronary syndrome (ACS) were included. Patients having angioplasty (PCI), coronary artery bypass surgery in the past and other co-morbid diseases were excluded. All patients were assessed for the presence of five components of metabolic syndrome including hypertension, HDL-Cholesterol and triglycerides, glucose intolerance and abdominal obesity. Systolic, diastolic blood pressures, waist circumference (WC) and body mass index (BMI) were measured. ECG, cardiac enzymes, fasting glucose and lipid profile were also done. Results: A total of 135 male patients of ACS were studied with a mean age of 54.26±11 years. Metabolic syndrome (MS) was present in 55 (40.7%) patients. MS with all five components was documented in 4 (7.27%) while MS with four and three components was seen in 23 (41.81%) and 28 (50.90%) patients respectively. Only 24 (43.63%) patients with MS had diabetes mellitus, remaining 31(56.36%) were non diabetic. Frequencies of diabetes, hypertension and family history of CAD were significantly higher (p<0.05) in patients with metabolic syndrome as compared to patients with normal metabolic status. Conclusion: Metabolic syndrome is fairly common and important risk factor in patients of IHD. Other risk factors like smoking, dyslipidemia, hypertension and diabetes were also frequently found. Public awareness to control the risk factors can reduce the prevalence of CAD in our country.